Ophthalmic Artery as a sensor for non-invasive intracranial pressure measurement electronic system - Bartusis, Laimonas; Zakelis, R.; Daubaris, G.; Ragauskas, A.; Rutkauskas, S.; Matijosaitis, V.; Preiksaitis, A. (Elektronika ir Elektrotechnika, 2012)
Theoretical and experimental validity of ophthalmic artery (OA), as a sensor for non-invasive absolute intracranial pressure (aICP) measurement electronic system is presented in this paper. Because of OA similarity with gravimetric scales which can compare aICP with non-invasively applied external pressure Pe the value of aICP can be measured without the need of patient specific calibration. For the indication of aICP and Pe balance various blood flow parameters existing in intracranial and extracranial segments of OA are used. Pressure balance ICP=Pe occurs in the case of maximum conjunction of various blood flow parameters in intracranial and extracranial segments respectively. For the measurement of the blood flow parameters and indication of aICP, specially designed hardware and software has been created in Telematics Scientific Laboratory of Kaunas University of Technology. This innovative non-invasive aICP measurement system is described in this paper. The software of non-invasive aICP meter was developed concerning the fast location of IOA and EOA and fully automatic aICP measurement process. Prospective comparative clinical studies of 84 neurological patients were performed in order to test performance of created system and to validate ophthalmic artery performance as non-invasive aICP sensor. Ill. 3, bibl. 13 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1194